Effects of hardness and toughness of ceramic in a ceramic armour module against long rod impacts - Goh, Wei Liang (2021)
A series of experiments and simulations were conducted to investigate the effects of hardness and toughness of ceramic on the ballistic performance of ceramic armour modules. The experiment was conducted using ceramics from 3M technical ceramic, using the tiles Grade T, T+, F and F+ with dimensions of 100 mm X 100 mm X 20 mm. These ceramic tiles were assessed using a simplified ceramic armour module consisting of the ceramic tile sandwiched between a cover plate and a backing plate. The test samples were made of either single tile module or multiple tile modules. They were tested against tungsten alloy long rod projectiles at a nominal velocity of 1250 m/s. Experimental results showed that ballistic performance of the ceramic correlated with hardness but not fracture toughness, based on mass efficiency. Fracture toughness correlated instead with the damage radius in the ceramic. Simulation using LS‐DYNA revealed that improved ballistic performance of the ceramic tiles was due to long dwell time. High fracture toughness of ceramics could suppress damage by tensile stress wave generated.